Heterogeneous effects of mass academisation in England - Lorenzo Neri; Elisabetta Pasini (Queen Mary University of London, School of Economics and Finance, 2018)
The 2010 primary school reform in the UK aimed at giving schools more autonomy and freedom from local council's control, by giving them the option to become academies. Once converted, schools need to choose between remaining a standalone academy or joining an academy chain. However, the majority of studies have focused solely on the impact of school conversion on children outcomes, disregarding the heterogeneity in the conversion models. In this paper we therefore evaluate the impact of the two different models of school governance on students' achievement. We exploit an instrumental variable strategy that compares the educational attainment of students before school conversion with that of students after conversion that were already enrolled when the conversion took place. We then allow for heterogeneous effects stemming from different governance models. We find that students enrolled in chains have higher test scores at the end of their primary school education. Survey data on academies suggest that schools belonging to chains are more likely to change leadership and entrust the governing body with purely managerial functions, while educational functions are carried out by the schools themselves.
Keywords: I20; I21; I28; 330; Academies; School governance; School performance; US states